The Influence of Learning Motivation on the Learning Outcomes of Students at the Madrasah Tsanawiyah Level - Andri Yanti, Novi; Masfufah, Masfufah (Journal of Islamic Elementary Education, 2025)
Education has a central role in improving the quality of human resources and the sustainability of a nation. The success of education is reflected in student learning outcomes which include cognitive, affective, and psychomotor aspects. One of the key factors that affect learning outcomes is learning motivation. Motivation functions as a driver and director of student learning activities that have a direct impact on the achievement of academic achievement. This article aims to examine the role of learning motivation on student learning outcomes at the MTS level equivalent. Through a literature review, it was found that high learning motivation can increase students' effort intensity, strengthen their enthusiasm for learning, and help students understand and apply knowledge in daily life. This research is expected to provide strategic recommendations in creating an effective learning environment based on religious values, in order to support the improvement of the quality of education as a whole.